PSD-Constrained PAR Reduction for DMT/OFDM - Krongold Brian S (EURASIP Journal on Advances in Signal Processing, 2004)
Common to all DMT/OFDM systems is a large peak-to-average ratio (PAR), which can lead to low power efficiency and nonlinear distortion. Tone reservation uses unused or reserved tones to design a peak-canceling signal to lower the PAR of a transmit block. In DMT ADSL systems, the power allocated to these tones may be limited due to crosstalk issues with many users in one twisted pair bundle. This PSD limitation not only limits PAR reduction ability, but also makes the optimization problem more challenging to solve. Extending the recently proposed active set tone reservation method, we develop an efficient algorithm with performance close to the optimal solution.